Phenotypic Switching of Staphylococcus aureus Mu50 Into a Large Colony Variant Enhances Heritable Resistance Against β-Lactam Antibiotics - Sun, Yajun; Liu, Miaomiao; Niu, Mingze; Zhao, Xin (Frontiers in Microbiology, 2021)
Phenotypic heterogeneity within a bacterial population may confer new functionality and allow microorganisms to adapt to fluctuating environments. Previous work has suggested that Staphylococcus aureus could form small colony variants to avoid elimination by therapeutic antibiotics and host immunity systems. Here we show that a reversible non-pigment large colony morphology (Mu50∆lcpA-LC) was observed in S. aureus Mu50 after knocking out lcpA, coding for the LytR-CpsA-Psr family A protein. Mu50∆lcpA-LC increased resistance to β-lactam antibiotics, in addition, the enlarged cell size, enhanced spreading ability on solid medium, and reduced biofilm formation, suggesting better abilities for bacterial expansion. Moreover, the expression of spa encoding protein A was significantly increased in Mu50∆lcpA-LC. This study shows that besides the small colony variants, S. aureus could fight against antibiotics and host immunity through phenotype switching into a large colony variant.